(untitled) (Research, Society and Development, 2020)
The objective of this work was to evaluate whether medicinal plants as active ingredients of herbal, homeopathic and floral medicines marketed in Brazil, had potential use as a therapeutic strategy for prevention, treatment and cure for COVID-19. This study took into account products marketed and regulated by Brazilian legislation with claims such as: immunomodulators, antivirals and improvement of symptoms related to respiratory system deficiency, which were calculated the absolute (n) and relative (%) frequencies. In addition, PubMed®, Web of Science® and SciVerse Scopus® databases were used to search the literature in order to obtain the scientific claims of plants found in the formulations of the evaluated products, taking into account the typical symptoms of COVID-19. 113 products were found, of which 65% were herbal medicines, 27% homeopathic medicines and 7% floral. There were 13 medicinal plants with an absolute frequency ≥ 5, in which scientific evidence was found regarding their medicinal use, as a complementary therapy in the treatment of symptoms related to COVID-19.